Artificial Intelligence Usage And Academic Integrity Challenges Among Higher Education Students: Penggunaan Kecerdasan Buatan Dan Tantangan Integritas Akademik Pada Mahasiswa Pendidikan Tinggi - Peny Husna Handayani; Gita Noveri Eza; Srinahyanti Srinahyanti; winda widya sari (Pedagogia : Jurnal Pendidikan, 2026)
General Background The rapid advancement of generative technologies creates profound transformations within modern university learning environments. Specific Background Undergraduates increasingly integrate platforms like ChatGPT to complete coursework, correct grammar, and optimize literature searches. Knowledge Gap Despite providing substantial cognitive assistance, excessive reliance on these digital instruments raises severe concerns regarding ethical violations, over-dependency, and the potential erosion of independent analysis. Aims This study investigates usage patterns, learner perceptions, and ethical considerations surrounding technology adoption across multiple teacher training disciplines. Results Quantitative survey data from 351 participants reveal that the vast majority actively utilize digital tools primarily to accelerate task completion. Concurrently, while acknowledging practical time-saving benefits, respondents express significant anxiety regarding their growing dependency and the subsequent decline in personal creativity and critical thinking. Novelty The research uniquely highlights the internal moral conflict experienced by learners, positioning the technology simultaneously as a valuable intellectual partner and a risky shortcut. Implications Educational institutions must formulate comprehensive regulatory guidelines and redesign authentic assessment strategies to foster ethical digital literacy while preserving human intellectual capacity. Highlights Survey data reveals that the vast majority of undergraduates rely on generative platforms to complete coursework assignments. Participants acknowledge significant time-saving benefits while simultaneously expressing concern over declining personal creativity and analytical skills. Institutions must formulate comprehensive regulatory guidelines and redesign assessments to foster responsible technology literacy. Keywords Artificial Intelligence; Academic Ethics; Generative Platforms; Digital Literacy; Critical Thinking